2015
DOI: 10.1007/s00330-015-3643-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased epicardial fat is independently associated with the presence and chronicity of atrial fibrillation and radiofrequency ablation outcome

Abstract: • Increased epicardial fat is associated with presence and chronicity of atrial fibrillation • Extensive epicardial fat is associated with earlier recurrences of AF after ablation • Extensive epicardial fat may reduce transmurality of ablation by affecting current dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Epicardial fat volume (EFV) has been correlated with numerous disease processes including coronary artery disease, atrial fibrillation and diabetes [1-5]. It has been demonstrated that epicardial fat is metabolically different from other visceral fat both biochemically and in terms of its correlation to cardiac risk factors [6-9].…”
Section: Introductionmentioning
confidence: 99%
“…Epicardial fat volume (EFV) has been correlated with numerous disease processes including coronary artery disease, atrial fibrillation and diabetes [1-5]. It has been demonstrated that epicardial fat is metabolically different from other visceral fat both biochemically and in terms of its correlation to cardiac risk factors [6-9].…”
Section: Introductionmentioning
confidence: 99%
“…Extrapericardial fat volume (EPFV) was calculated as a difference between ITFV and EFV (Fig 2). We previously showed no significant inter-reader variability in intrathoracic fat measurements (13,32). …”
Section: Methodsmentioning
confidence: 86%
“…All patients were premedicated with one puff of sublingual nitroglycerin 1–5 minutes before scanning, and only patients with a heart rate over 65 beats per minute received 100 mg metoprolol orally 60 minutes before CT. CT calcium scoring technique used cine mode with scan parameters that included 0.35-second gantry rotation speed, 2.5-mm slice thickness, and 120 kVp, adjusted for patient size. CCTA portion with IV contrast was previously described (13,32). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations